2020
DOI: 10.3390/ani10071129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Blood Types and Alloantibodies of the AB Blood Group System in Non-Pedigree Cats from Northern (Lombardy) and Southern (Sicily) Italy

Abstract: The aims of this study were to determine the prevalence of A, B and AB blood types and alloantibodies in non-pedigree cats from two regions, one in Northern and one in Southern Italy (Lombardy and Sicily, respectively). A total of 448 samples (52.0% from Northern and 48.0% from Southern Italy) were blood typed. The prevalence of A, B and AB blood types in northern and southern cats were 91.0%, 5.2%, 3.8%, and 77.2%, 12.1% and 10.7%, respectively. The prevalence of type-A blood in southern cats was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 44 publications
6
16
1
1
Order By: Relevance
“…In this study, the blood type AB was quite low (3.1%) and this result is in contrast with the high incidence identified in Southern Italy in a recent study [ 16 ]. To the author’s knowledge, this result is similar to that reported in most other studies with the exception of Portugal, Germany, and UK where a frequency of 6.3%, 7.4%, and 8.5% in mixed breed cats was reported, respectively [ 8 , 17 , 25 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, the blood type AB was quite low (3.1%) and this result is in contrast with the high incidence identified in Southern Italy in a recent study [ 16 ]. To the author’s knowledge, this result is similar to that reported in most other studies with the exception of Portugal, Germany, and UK where a frequency of 6.3%, 7.4%, and 8.5% in mixed breed cats was reported, respectively [ 8 , 17 , 25 ].…”
Section: Discussioncontrasting
confidence: 99%
“…As reported in Table 1 , in this survey the frequency of type B in the feline population is higher (7.0%) compared to most other European studies (i.e., Croatia, Denmark, Finland, Hungary, Iberian Peninsula, Switzerland, and UK) [ 2 , 3 , 5 , 10 , 11 , 17 , 18 , 19 , 21 ] and is comparable to those of four studies conducted in Northern Italy, where about a total of 600 European domestic shorthair cats were enrolled [ 13 , 14 , 15 , 16 ]. Instead, Giger et al and Spada et al reported a high prevalence of blood type B in Central (11.2% in Tuscany region) and Southern Italy (12.1% in Sicily), respectively [ 5 , 16 ]. Although in most reports from other European areas the prevalence of group B in non-pedigree cats is also low (less than 10%), there are marked geographical variations.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations